2021
DOI: 10.1371/journal.pone.0248122
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid burden quantification depends on PET and MR image processing methodology

Abstract: Quantification of amyloid load with positron emission tomography can be useful to assess Alzheimer’s Disease in-vivo. However, quantification can be affected by the image processing methodology applied. This study’s goal was to address how amyloid quantification is influenced by different semi-automatic image processing pipelines. Images were analysed in their Native Space and Standard Space; non-rigid spatial transformation methods based on maximum a posteriori approaches and tissue probability maps (TPM) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, Kolinger et al compared the impact of the reference space for analysis on the SUVr and found no significant difference between native and standard space, but any image feature using volumetric information should be performed in native space. 184 With the increasing availability of longitudinal registration pipelines for structural MRI, a few studies have begun to implement them into longitudinal analysis of amyloid and tau PET data. 26,39,54,66,185 Longitudinal registration pipelines are available in SPM, 179 FreeSurfer, 16 and ANTs.…”
Section: Joint Image Processingmentioning
confidence: 99%
“…However, Kolinger et al compared the impact of the reference space for analysis on the SUVr and found no significant difference between native and standard space, but any image feature using volumetric information should be performed in native space. 184 With the increasing availability of longitudinal registration pipelines for structural MRI, a few studies have begun to implement them into longitudinal analysis of amyloid and tau PET data. 26,39,54,66,185 Longitudinal registration pipelines are available in SPM, 179 FreeSurfer, 16 and ANTs.…”
Section: Joint Image Processingmentioning
confidence: 99%
“…However, accurate measurement and cut-off values are highly dependent on the chosen tracer, reference region (Fig. 2 ), and delineation method [ 74 , 129 , 130 ], which challenges the pooling of multi-centre SUVr data across tracers [ 131 ]. In addition, there is high variability in longitudinal results [ 93 , 132 ], which limits the power in detecting genuine biological differences.…”
Section: Quantitative Measures For Clinical Assessment Of Amyloid Burdenmentioning
confidence: 99%
“…To combat this, the field is pushing towards standardization of imaging acquisition and processing methods ( Mueller et al, 2005 ; Whitesell et al, 2019 ). Even when using identical mouse models and similar imaging approaches, independent labs can achieve varying results for measures like rate of amyloid plaque accumulation or regional levels of atrophy ( Kolinger et al, 2021 ; Mannheim et al, 2018 ; Morbelli and Bauckneht, 2018 ; Osborne et al, 2017 ). This lack of consistency makes it difficult to combine and compare results, and for these reasons, all processing parameters should be disclosed to promote reproducibility ( Eisenstein, 2020 ).…”
Section: Future Directions Of Systems Biology and Use Of Imaging Moda...mentioning
confidence: 99%